The influence of service quality and price on consumer satisfaction - Cahyani, Ananda; Dipayanti, Kris (Indonesian Development of Economics and Administration Journal, 2025)
This study aims to determine the effect of service quality and price on consumer satisfaction at the Cafe Teras Kayoe in Balaraja, Tangerang Regency. Methodology/approach – This research method uses a quantitative approach, an associative research type. The study population consisted of 15,404 consumers, and a sample of 99 respondents using probability sampling techniques. Findings – The results of the study show that service quality and price have a positive and significant effect on consumer satisfaction. Novelty/value – The correlation coefficient is a very strong relationship, and the determination coefficient is 74.7%, The hypothesis test results show that Fcount > Ftable or 141.956 > 3.09 with a significance value of 0.000 < 0.05. Thus, service quality and price have a positive and significant effect on customer satisfaction.